1999
DOI: 10.1146/annurev.ento.44.1.131
|View full text |Cite
|
Sign up to set email alerts
|

Odor-Mediated Behavior of Afrotropical Malaria Mosquitoes

Abstract: The African mosquito species Anopheles gambiae sensu lato s.l. and Anopheles funestus rank among the world's most efficient vectors of human malaria. Their unique bionomics, particularly their anthropophilic, endophagic and endophilic characters, guarantee a strong mosquito-host interaction, favorable to malaria transmission. Olfactory cues govern the various behaviors of female mosquitoes and here we review the role of semiochemicals in the life history of African malaria vectors. Recent evidence points towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
610
2
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 619 publications
(624 citation statements)
references
References 139 publications
8
610
2
4
Order By: Relevance
“…2). These results emphasised the idea that the biting behaviour of R. prolixus, similarly to Anopheles gambiae (Takken & Knols 1999, Enserink 2002, Verhulst et al 2009), is not a random process and is clearly influenced by the bacteria present on the skin. The importance of the Rhodnius-bacteriahuman face interaction was confirmed here for Chagas disease transmission (Figs 2, 3).…”
Section: Discussionmentioning
confidence: 71%
“…2). These results emphasised the idea that the biting behaviour of R. prolixus, similarly to Anopheles gambiae (Takken & Knols 1999, Enserink 2002, Verhulst et al 2009), is not a random process and is clearly influenced by the bacteria present on the skin. The importance of the Rhodnius-bacteriahuman face interaction was confirmed here for Chagas disease transmission (Figs 2, 3).…”
Section: Discussionmentioning
confidence: 71%
“…More recently, Mukabana et al (2004) reported allomonal activity of human breath, which would explain why differences in the quantity of expired CO 2 (Brady et al, 1997) would result in variation in human attractiveness. Other factors considered to cause variation in attractiveness between individuals are differences in skin composition and microbial flora on the human skin (Knols, 1996;Takken and Knols, 1999).…”
Section: Behavior and Sensory Physiologymentioning
confidence: 99%
“…Indeed, the chemical ecology of mosquitoes is now widely recognized as one area of investigation on which future control strategies may depend. Host seeking and feeding behaviors are much affected by host odors, and many mosquito species use olfaction for oviposition (Takken and Knols, 1999). It is not known, though, whether mating is also mediated by smell, although there is indirect evidence that for at least a few species an olfactory component is involved in mating.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10] The molecules in the cloud penetrate in their cuticular pores and are captured by the olfactory binding proteins (OBP). Next, these molecules are transported to the olfactory receptor neurons (ORN), located in the dendritic membranes at the antenna sensory bristles, driving the mosquito's attention to the potential meal.…”
Section: Introductionmentioning
confidence: 99%